Trade Flows Among CEEC and EU Countries: What are the Future Perspectives? - Caetano, José (2012)
In this paper we analyse the characteristics and evolution of the EU-CEEC trade in the last decade, giving particular attention to trade relations among the CEEC. We study the determinants of both total and sectoral trade flows and investigate the potential bilateral trade among all the countries. The analysis is based on the gravity model approach using panel data from 1993 to 2001. The results highlight the sectoral differences in the EU-CEEC trade developments. Furthermore, it is possible to conclude that there is still scope for growth on bilateral trade flows between some CEEC and some of the EU countries and especially among the new EU members.